Sexual behaviour of pregnant women attending antenatal care clinic at Assiut Women's Health Hospital, Egypt - Bahloul, Mostafa; Othman, Ahmed M.; Abbas, Ahmed M.; Salman, Safwat A.; Sayed, Gamal H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The aim of the current study was to describe the knowledge, attitudes, beliefs and behavior of pregnant women regarding sexuality during pregnancy. Study was carried out at Women’s Health Hospital, Assiut University, Egypt. Methods: A cross-sectional study included pregnant women at different gestational ages between December 2016 and Jun 2017 recruited consecutively at the antenatal outpatient clinic of women’s Health Hospital at Assiut University. We used the Arabic version of the Female Sexual Function Index (Ar-FSFI) in the interview to evaluate the sexual functions or problems during the last month. The cut-off score used to indicate sexual dysfunction was 28.1. The obtained data were analyzed by means of SPSS software (version 22.0) and p<0.05 was taken as the significant level. Results: The study included 140 pregnant women at different ages and trimesters and also at different socio-economic states. Concerning the level of knowledge, the classification in recorded a mean score =11.91±4.05 which revealed a level of knowledge below average. Regarding the extent of beliefs in relation to sexuality during pregnancy, the mean score=2.72 of the respondents’ beliefs means that the impact of the beliefs regarding sexuality during pregnancy was weak among respondents. On assessing their perceptions about sexual intercourse during pregnancy, majority of them [130 (93.1%)] felt that sex have no negative impacts on pregnancy while 10 (6.9%) opined that sex during pregnancy had negative effects. Perceived negative effects of sex during pregnancy included vaginal bleeding and miscarriage. Conclusions: The low rate of sexual activity in our study, regardless question about the taboo of sexual intercourse during pregnancy, could be related to a cultural background in which women avoid speaking about their desires and sexual needs.